Analysis of Corn Farmer Income in Sondoang Village, Kalukku District Mamuju Regency - Masita, Masita; Halim, Abdul; Mappigau, Ernawaty (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This research aims to analyze the income of corn farmers in Sondoang Village, Kalukku District, Mamuju Regency, and to assess the role of government interventions in increasing their income. The study employs qualitative and quantitative methods, involving direct interviews with key stakeholders such as the village government, agricultural extension workers, and local farmers. Data collection methods include interviews, observations, and documentation, validated through triangulation techniques (source, technical, and time triangulation). Results indicate that government support, in the form of seed provision and agricultural extension programs, significantly impacts farmer productivity and income. This research highlights the potential of corn farming as a sustainable income source for rural communities and the critical role of government facilitation in enhancing agricultural practices.